Senecio inaequidens DC. (Compositae, Senecioneae), a noxious weed introduced to Mexico - Rzedowski, Jerzy; Vibrans, Heike; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2003)
Senecio inaequidens DC., a weed of South African origin, is reported from 10 localities of central Mexico. In most places the populations are small and apparently of recent arrival. However, in the vicinity of the town of Amealco, situated in the southern extreme of the state of Querétaro, the species is extremely abundant in ruderal environments and apparently has existed there for 50 or more years. his paper summarizes information concerning uncertainty of the identification of the species, particularly in connection with the use of the name Senecio madagascariensis Poir. It includes also some outstanding aspects of its geographical distribution and of the history of its invasion in central and southern Europe, Australia and Argentina, where in recent decades the plant has become a severely noxious weed, especially in cattle raising areas, and also a dangerous competitor of native plants in some natural environments.  description and illustrations of the species are included, as well as a discussion of its ecological and agronomic relevance.